Originally Posted by
billym Sorry, I'm trying to isolate x, not y.
I have :
x^2 = (e^(y + 1/2(y^2) + C)^2) - 1
Mr F says: $\displaystyle \sqrt{1 + x^2} = e^{y + \frac{y^2}{2} + C} \Rightarrow 1 + x^2 = (e^{y + \frac{y^2}{2} + C})^2 = e^{2 \left( y + \frac{y^2}{2} + C \right)} = e^{2y + y^2 + 2C} $
(let e^C = D)
Mr F says: No. Let $\displaystyle e^{2C} = D$. Therefore $\displaystyle 1 + x^2 = D e^{2y + y^2} \Rightarrow x^2 = D e^{2y + y^2} - 1$.
And when you take the square root it'll be $\displaystyle x = \pm ........ $.
x = sqrt ((D*e^y*e(1/2(y^2))^2 - 1))
Is this correct?